Conservative management of placenta increta: a review - Kwaśniewska, Anna; Stupak, Aleksandra (Menopause Review/Przegląd Menopauzalny, 2010)
Placenta increta is an effect of abnormal implantation in decidua or in myometrium. This condition is rare in obstetrical practice but related with about 7% mortality among the parturient. The pathology of placenta complicates, according to different sources, 1/533 to 1/40000 pregnancies. In relation to an increasing number of caesarean sections the number of placenta increta is growing. The pathogenesis of placenta increta is multidimensional and still unknown. The diagnosis and treatment represent an important clinical problem. The diagnosis can be made on the basis of the clinical condition, ultrasound with Color-Doppler and magnetic resonance. The possibilities of operative treatment include hysterectomy as well as resection of the uterus wall and occlusion of uterine arteries. Conservative management relies on administration of methotrexate in different doses. The latest methods involving mifepristone, misoprostol and gonadotrophin-releasing hormone analogues are an extremely interesting alternative. Since there is no standard protocol of clinical treatment every qualification to this type of treatment should be considered carefully.